Radiological Assesment of Non-Traumatic Acute Abdomen - Ahir, Hetal; Happani, Hiral; Trivedi, Anjana (Asian Journal of Medical Radiological Research, 2023)
The acute abdomen refers to the presence of an acute attack of abdominal pain, which may occur suddenly or gradually over a period of several hours, induced by a wide variety of pathological conditions that may require medical or surgical intervention. Patients with acute abdomen are among the largest group presenting into emergency department. Conventional radiography is particularly effective in detecting bowel distention, free intraperitoneal air, abnormal calcification and air fluid levels. Ultrasound however has a valuable role in lesions involving hepatobiliary system, kidney, appendix and pelvis abnormal fluid collections like hemoperitoneum, peritonitis, abscess etc. Ultrasound has become firmly established as a useful, safe, non-invasive, portable means in evaluating patients with acute abdominal pain. CT scan is particularly useful in evaluation of patients with equivocal sonographic findings or for better evaluation of conditions already diagnosed by ultrasound. Now a day more number of patients presenting with acute abdomen are investigated radiologically for earlier and more detail preoperative diagnosis. surgery has become more safe and curative.